Memunjung, a feast for the dead - Putu Herry Hermawan Priantara (Bali Tourism Journal, 2018)
Memunjung is a form of respect and solidarity with the deceased.It realizes by the family visiting their late relative in cemetery,then spend their time having meals together with the dead. Thetradition has been practicing since the Hindu-Buddhist period. Itis well developed both in Java and Bali. The community practicesthis activity on certain days, such as Galungan, Kuningan andPagerwesi day while in Java, they carry out Memunjung duringholidays such as Idul Fitri. Balinese Hindu offers Tampelan punjungand Banten punjung to the spirit of ancestors, families or relatives athome or cemetery. In certain days, the visitor brings the deceased’sfavorite food to the cemetery then they enjoy the meal togetherwith the dead. Recently, the custom to visit the grave is rarely doneby Balinese, especially to those who live in regional areas that donot have strict rules about burial. Some argue that the increasingBalinese’s standard of living as well as technological advancements,contribute to change people mindset about the funeral in thepresent. Hence, there are only a few areas that are still practicingburial for the dead.